Ghana yam exports surge ahead - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Ghana s efforts to increase yam exports are paying off. With yam one of its principal crops, Ghana is the world s second largest producer of the root, with 3.25 million tonnes grown in 1999. In 1998 it exported 7,500 tonnes of yam, mainly to the...